Associations between breastfeeding duration and overweight/obese among children aged 5-10: a focus on racial/ethnic disparities in California - Christian E. Vazquez; Catherine Cubbin (AIMS Press, 2019)
Research on the association between breastfeeding and childhood obesity and research on racial/ethnic differences in breastfeeding both show inconsistencies. The current study examines: 1) whether immigrant Hispanic women have higher rates of breastfeeding compared to non-Hispanic (three separate groups: African-American, Asian/Pacific Islander, and White) and U.S.-born Hispanic women; 2) whether children who were breastfed are less likely to be overweight/obese compared to children who were not breastfed; and 3) whether associations between breastfeeding and weight status vary by race/ethnicity/nativity. The study builds on prior literature using representative data from the Geographic Research On Wellbeing study (GROW, 2012-2013) and focusing on ages 5-10 years, an age group that has not been well studied (N = 2675 mother/child dyads). Logistic regression was used to investigate the odds of child obesity (≥95th%) and child overweight (≥85th%) in a series of models: unadjusted (each variable individually), demographic (child's sex, child's age, mother's age, mother's race/ethnicity, and mother's marital status), socioeconomic status (mother's education and family income), and full model (mother's BMI); with breastfeeding included in all models. Interactions between race/ethnicity and breastfeeding duration were also examined. African-American (9.54%) and white (32.8%) women had the lowest and highest rates of ever breastfeeding, respectively. White women breastfed the longest (M = 10.52 months, SE = 0.028) and U.S.-born Hispanic women breastfed the shortest (M = 7.05 months, SE = 0.41), on average. Children of African-American and U.S.-born Hispanic mothers had higher odds of being overweight/obese (74-75%) compared with children of white mothers. No associations were found between breastfeeding duration and child's weight status in adjusted models, nor was there a significant interaction between mother's race/ethnicity and breastfeeding duration on child's weight status; however, mother's own weight status was a significant driver of child's weight status and explained the racial/ethnic disparities. These results provide evidence in favor of there being no association between breastfeeding and childhood obesity.